PENGARUH KUALITAS PRODUK, PROMOSI, DAN PERSEPSI HARGA TERHADAP MINAT BELI BERULANG SEPATU VENTELA - Hadis Saputra; Ravindra Safitra Hidayat (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
This study aims to determine the effect of price perception, promotion, and product quality on repurchase intention of Ventela shoes among students of the Faculty of Economics and Business, Universitas Budi Luhur. This research uses a quantitative method with a total sample of 100 respondents. The sampling technique used is non-probability sampling with purposive sampling method, and the sample size was determined using the Lemeshow formula. Data were collected through questionnaires using a Likert scale and processed using Microsoft Excel 2021 and SPSS version 26. The data analysis techniques include validity and reliability tests, classical assumption tests, multiple linear regression analysis, coefficient of determination, and hypothesis testing. The results show that price perception, promotion, and product quality have a positive and significant effect on repurchase intention. Product quality is the most dominant variable influencing repurchase intention.